Effects of Cardiovascular Health Shocks on Spouses' Work and Earnings: A National Study. Issue 2 (February 2020) - Jeon, Sung-Hee; Stepner, Michael; Rotermann, Michelle; Fransoo, Randy; Sanmartin, Claudia; Scales, Damon C.; Wunsch, Hannah; Iwashyna, Theodore J.; Garland, Allan
Abstract : Background: Acute health shocks can reduce the ability to work and earn among working-age survivors. The full economic impact includes labor market effects on spouses/partners, but there is a knowledge gap in this area. Objectives: The objective of this study was to assess how 3 common health shocks, acute myocardial infarction, stroke, and cardiac arrest, influence work and earnings of spouses aged 35–61 years. Research Design: This retrospective cohort study of case and control couples used population-based, linked Canadian income tax and hospitalization data from 2005 to 2013. Subjects: Case couples comprised 1 partner aged 41–61 years who experienced a health shock in the index year and survived 3 years hence, and a working-age partner. Control couples were matched up to 5:1 on 12 characteristics, with neither experiencing the health shock of interest in the index year. Measures: Primary outcome was the change in spousal annual earnings between the year prior and 3 years after the event. Pre-to-post spousal income changes were categorized into 9 levels and compared between case spouses and control spouses by the Pearson χ 2 test. Results: There were 11, 208 matched case couples for acute myocardial infarction, 622 for cardiac arrest, and 2288 for stroke. Overall, case and control spouses experienced similar distributional changes in preevent to postevent earning (all P ≥0.27). Heterogeneity analysis indicated that spouses of more severe stroke sufferers ceased working at a higher rate than for control spouses. Conclusion: Beyond assessing average values, detailed analysis of changes in spousal earnings after common cardiovascular health shocks did not demonstrate effects attributable to those health shocks. Abstract : Supplemental Digital Content is available in the text.